Development and In-Vitro Evaluation of Citicoline Sodium and Risperidone Controlled Release Tablets for Bipolar Disorder - Rayakwar, Neetesh; Malik, Jitendra Kumar; Singh, Surendra Pratap; Jhariya, Deepak; Arya, Sunita (Journal of Neonatal Surgery, 2025)
Bipolar disorder poses major treatment challenges, which demand novel drug delivery strategies to provide the most effective treatment with minimal side effects. The objective was to prepare and evaluate controlled release tablets of citicoline sodium and risperidone for improved treatment in management of bipolar disorder. The multiparticulate (combination therapy) was prepared by wet granulation process with the matrix polymers hydroxypropyl methylcellulose (HPMC K100M) and ethyl cellulose. Nine formulations of different drug-to-polymer ratios were prepared and characterized. The technique included qualifying pre compression characteristics, post compression features, and in vitro dissolution studies employing USP Apparatus II. It was concluded from the results that formulation F7 with 30% HPMC and 60% ethyl cellulose showed best controlled releasing behavior i.e., 89.4% drug release at the end of 12 hours according to zero-order release kinetics. The drug's release profile was neutral pH independent and uniform throughout the range of media tested. Release rate was found to have comparable relationship with polymer concentration (p<0.05). The resulting formulation exhibited good bioavailability potential with less dosing frequency. This study successfully shows the potential of a controlled release combination therapy for bipolar disorder treatment to achieve sustained drug release, leading to reduced side effects, and, in turn, enhance the treatment compliance and therapeutic efficacy